1949
DOI: 10.1039/tf9494501032
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aromatic compounds on the vapour-phase oxidation of fuels. Part I.—the effect on the vapour-phase oxidation of ethers

Abstract: The effects of a wide range of aromatic additives on the vapour-phase slow oxidation of diisopropyl ether at 360" C are reported. It is found possible to correlate the efficacy of the inhibiting action with the electronic properties of the benzene ring in the inhibitor. Experiments are also reported on the effects of aromatic additives on the slow oxidation of diisopropyl ether in the cool flame temperature range and on the ignition of diethyl ether t o both cool and hot flames. It appears that aromatic inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1951
1951
1977
1977

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Acetaldehyde, another product, has little or no influence on the induction period at 153 °C, but it increases the rate of the second part of the reaction (table 3). The failure of acetaldehyde to markedly change the kinetics of the reaction is in agree ment with earlier results (Chamberlain & Walsh 1949 a).…”
Section: Influence Of Added Productssupporting
confidence: 92%
See 2 more Smart Citations
“…Acetaldehyde, another product, has little or no influence on the induction period at 153 °C, but it increases the rate of the second part of the reaction (table 3). The failure of acetaldehyde to markedly change the kinetics of the reaction is in agree ment with earlier results (Chamberlain & Walsh 1949 a).…”
Section: Influence Of Added Productssupporting
confidence: 92%
“…Such an attack on the ether molecule has already been predicted (Townend & Chamberlain 1937;Chamberlain & Walsh 1949 a). Reaction between ether and oxygen can be inhibited readily by small additions of a negative catalyst (Chamberlain & Walsh 1949a, b, 1952Lemay & Ouellet 1957;Waddington 1959), and thus t bimolecular reaction is probably infrequent. Hence, the formation of ether radicals may also be effected by the attack on ether molecules by oxygenated radicals (Lemay & Ouellet 1955).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…aromatic compounds with unsaturated side chains such as styrene, some conjugated diolefins) are just the fuels which one would expect (because of self-inhibition ; see ref. (15)) to oxidize by many very short chains and so to be relatively little affected by an inhibitor destroying chain carriers, leaving the (normally masked) small promoting effect a clear field in which to reveal itself. It has in fact long been practically certain that inhibition by lead tetraethyl is primarily due to the metallic part of the molecule since very early experiments showed that (a) the vapour from a lead arc drawn into the air intake of an engine,lG (6) colloidal solutions of lead in petrol,l7 could exert a strong anti-knock effect.…”
Section: Earlier Theories Of Action-(i)mentioning
confidence: 99%
“…Hand in hand with the engine experiments, extensive work has been proceeding on combustion in a glass apparatus (Chamberlain & Walsh 1949Malherbe & Walsh 1950). The engine and non-engine investigations are complementary, and each has helped the understanding of the other.…”
mentioning
confidence: 99%